University quality and graduate wages in the UK - Iftikhar Hussain; Sandra Mcnally; Shqiponja Telhaj (Institute for the Study of Labor (IZA), 2009)
We examine the links between various measures of university quality and graduate earnings in the United Kingdom. We explore the implications of using different measures of quality and combining them into an aggregate measure. Our findings suggest a positive return to university quality with an average earnings differential of about 6 percent for a one standard deviation rise in university quality. However, the relationship between university quality and wages is highly non-linear, with a much higher return at the top of the distribution. There is some indication that returns may be increasing over time.
urn:nbn:de:101:1-20090323117
Keywords: I23; J24; 330; University quality; returns to education; Hochschule; Dienstleistungsqualität; Bildungsertrag; Akademische Berufe; Großbritannien